COMPLEX ASSESSMENT OF RISK FACTORS FOR PRECISE CHOICE OF REVASCULARIZATION STRATEGY IN ST ELEVATION MYOCARDIAL INFARCTION AND MULTIVESSEL CORONARY DISEASE - R. S. Tarasov; V. I. Ganyukov; E. S. Kagan; O. L. Barbarash; L. S. Barbarash (Российский кардиологический журнал)
Aim. Invention of the model of differentiated strategy selection of revascularization in acute myocardial infarction with ST elevation (STEMI) and multivessel disease (MVD).Material and methods. Totally, 327 patients with STEMI and MVD included, undergoing primary transcutaneous coronary intervention (PCI). Patients were selected into 2 groups: (1) Multivessel stenting (MVS) during primary PCI (n=91); (2) Staged revascularization (SR) (n=236). The endpoints for 12 months follow-up were significant adverse cardiovascular events. Inside every group the relative level of an adverse outcome was calculated and prognostic coefficient invented that makes possible to estimate significance of every including clinical and demographic and angiographic parameter in the development of adverse outcome.Results. The most negative prognostic significance for adverse outcome in patients undergoing MVS for primary PCI had the following factors: (1) post infarction cardiosclerosis, (2) severe coronary atherosclerosis (SYNTAX ≥23 points), (3) older age (≥65 y.o.), (4) female gender. Concerning SR: (1) anamnesis of stroke, (2) post infarction cardiosclerosis, (3) multifocal atherosclerosis, (4) three-vessel coronary disease (5) non-drug eluting stents.Conclusion. Taking into account the complex of clinical and demographic, anatomic and angiographic factors facilitates the improvement of treatment results in STEMI by defining of optimal revascularization strategy.